The Implementing Joint Custody Post Divorce In Indonesia: a Philosophical Viewpoint - Triyono, Nur; Asmuni, Asmuni (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2023)
Child custody encompasses parental rights and responsibilities for raising and nurturing their children. In Indonesia, child custody often triggers disputes, especially in divorce cases. This research seeks to present a fresh perspective by examining the deconstruction of joint custody within the context of child guardianship. This study, focusing on legal aspects, employs a comparative approach to deconstruction concepts, drawing from Jacques Derrida's radical deconstruction and Thaha Abdurrahman's ethical deconstruction. The analysis aims to unearth possibilities and offer recommendations for implementing Joint Custody in Indonesia, particularly regarding post-divorce parental custody regulations. Both deconstruction concepts challenge the conventional maternal role in child custody, especially for children under 12. Embracing this deconstruction opens the door to considering joint custody as a new norm in Indonesia. Joint custody is no longer just a concept; empowering judges to consider it based on court proceedings is the fastest route to its adoption in the child's best interest. Keywords: joint custody; post-divorce; child custody.